Hepatitis B Virus Infection among Japanese Immigrants and Descendants: The Need to Strengthen Preventive and Control Measures - Luiz Henrique Ferraz Demarchi; Larissa Melo Bandeira; Deborah Ledesma Taira; Marina Castilhos Souza Umaki Zardin; Mary Luizia Ibanhes; Ana Olivia Pascoto Esposito; Larissa Domingues Castilho De Arruda; Crhistinne Cavalheiro Maymone Gonçalves; Sabrina Moreira dos Santos Weis-Torres; Gabriela Alves Cesar; Rivaldo Venâncio Da Cunha; Tayana Serpa Ortiz Tanaka; et al. (Viruses, 2022)
This cross-sectional study aimed to investigate the prevalence and risk factors of Hepatitis B virus infection among Japanese immigrants and their descendants from São Paulo (SP), and to verify the occurrence of occult hepatitis B and coinfection with HCV, Delta, and HTLV. All samples (n = 2.127) were tested for HBV serological markers by electrochemiluminescence. HBsAg and/or total anti-HBc positive samples were tested for HBV DNA by real-time PCR, and genotyped by sequencing using the Sanger methodology. The prevalence rate of HBV exposure was 13.4% (CI 95%: 11.9–14.9%), and 22 (1.1%) were HBsAg positive. A high rate of susceptibility to HBV infection was found (67.4%; CI 95%: 65.4–69.4%). In contrast, only 19.2% (CI 95%: 17.6–20.9%) presented a serological profile analogous to that elicited by Hepatitis B vaccination. HBV isolates (n = 8) were classified as genotypes HBV/B1 (62.5%), HBV/C2 (12.5%), HBV/F1b (12.5%), and HBV/A1 (12.5%). Hepatitis B vaccination strategies and educational measures to control this infection should be considered.